2014
DOI: 10.1016/s2095-4956(14)60110-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrolysis of ammonia for hydrogen production catalyzed by Pt and Pt-Ir deposited on nickel foam

Abstract: Electrolysis of ammonia in alkaline electrolyte solution was applied for the production of hydrogen. Both Pt-loaded Ni foam and Pt-Ir loaded Ni foam electrodes were prepared by electrodeposition and served as anode and cathode in ammonia electrolytic cell, respectively. The electrochemical behaviors of ammonia in KOH solution were individually investigated via cyclic voltammetry on three electrodes, i.e. bare Ni foam electrode, Pt-loaded Ni foam electrode and Pt-Ir loaded Ni foam electrode. The morphology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Recently, a considerable effort has been devoted to developing high‐performance Pt‐based electrocatalysts that are able to effectively enhance ammonia electro‐oxidation kinetics, and simultaneously, significantly decreasing Pt loading through applying Pt‐based bimetallic nanoparticles, constructing special structure or morphology, and dispersing nanoparticles on the appropriate substrate ,,. In general, alloying Pt with other metals causes a series of geometric and electronic effects resulting in the enhancement of electrocatalytic activity of Pt .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a considerable effort has been devoted to developing high‐performance Pt‐based electrocatalysts that are able to effectively enhance ammonia electro‐oxidation kinetics, and simultaneously, significantly decreasing Pt loading through applying Pt‐based bimetallic nanoparticles, constructing special structure or morphology, and dispersing nanoparticles on the appropriate substrate ,,. In general, alloying Pt with other metals causes a series of geometric and electronic effects resulting in the enhancement of electrocatalytic activity of Pt .…”
Section: Introductionmentioning
confidence: 99%
“…Sufficient ammonia is adsorbed on the catalyst surface at the beginning of electrolysis,b ut as electrolysis proceeds, the www.chemsuschem.org adsorbed ammonia is consumed to satisfy the appliedc urrent, thus creatingascarcityo fa dsorbed ammonia, which finally leads to the reaction characterizedb yt he evolution of oxygen. [1] The flow rate of gas production emitted from the cathode at variousc onstant-current conditions was measured using ab ubble flow meter;t he gas was qualitativelya nalyzed by gas chromatography (GC, Figure 7b). Through aq ualitativea nalysis of gas production,i tw as demonstrated that only hydrogen is emitted at the cathode from ammonia electrolysis.…”
Section: Resultsmentioning
confidence: 99%
“…[1] Hydrogen attracts increasing interesta sa na lternative energy source (theoretical energy density of hydrogen = 141 kJ g À1 ). [2,3] Despite the numerous advantages of hydrogen as an alternative energy source,e fficient hydrogen production from water,h igh pressure storage, andt ransportation remain very difficult.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6a and b showed the SEM images of Pt/NPC800 at different magnifications. It was observable that Pt slice-like aggregates [56] had successfully loaded on NPC800 through electrodeposition and the average size of Pt particles was about 1 lm. It was worthy of noting that Pt particles mainly deposited on NPC800 other than glassy carbon electrode substrate, which was possibly due to the stabilization of Pt particles by NPCs.…”
Section: Deposition Of Pt On Npc800mentioning
confidence: 99%